A Novel Four-Dimensional Hyperchaotic System: Design, Dynamic Analysis, Synchronization, and Image Encryption - Ozpolat, Erman; Celik, Vedat; Gulten, Arif (Ieee-Inst Electrical Electronics Engineers Inc, 2024)
This study comprehensively examines the design, dynamic analysis, and various application areas of a novel four-dimensional hyperchaotic system, which has not been previously utilized in the literature. The dynamic properties of the proposed hyperchaotic system are analyzed in detail, including bifurcation diagrams, Lyapunov exponents, phase diagrams, and sensitivity to initial conditions. The system behaves in a hyperchaotic manner, as verified by the dynamic analysis. Additionally, the physical feasibility of the system is tested through circuit simulations performed on the Multisim 14.3 platform. Within the scope of the study, synchronization of the proposed hyperchaotic system is achieved using active control methods, and the system is successfully applied in image encryption and decryption application. In this context, the advantages of hyperchaotic systems in terms of encryption security are emphasized. The obtained results demonstrate that the proposed four-dimensional hyperchaotic system can be effectively used in image encryption applications, offering significant potential in this field. This study can be considered an important step towards enhancing the role and effectiveness of hyperchaotic systems in secure communication implementations.
Keywords: Synchronization; Encryption; Chaotic communication; Bifurcation; Circuit simulation; Integrated circuit modeling; Time series analysis; Chaos; hyperchaotic system; active control synchronization; image encryption